The effectiveness of colour used in branding KIP Mart Hypermarket / Siti Nurfarahin Hasan - Hasan, Siti Nurfarahin (2015)
Color sells products. It is a powerful marketing tool that significantly influences consumer purchases, so much so that it accounts for 85% ofthe reason why someone decides to purchase a product (Hemphill 275). Marketers must understand the psychology of color in order to use iteffectively. Humans associate colors with meanings. These associations are studied extensively in marketing research. This paper explores how the psychology of color influences purchasing behavior as it pertains to product design, company branding, and the consumer. Nearly all products sold today have colorful facades. Selecting the right colors to use has an enormous impact on product sales. While no single set of rules governs color choices, research has established general guidelines based on the principle of associative learning, the relationship between color and emotion.